2007
DOI: 10.1111/j.1398-9995.2006.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relation between nasal fluid Clara Cell Protein 16 levels and symptoms and signs of rhinitis in allergen‐challenged patients with intermittent allergic rhinitis

Abstract: There was an inverse relation between nasal fluid CC16 levels and symptoms and signs of rhinitis in allergen-challenged patients with IAR. However, there was no association between IAR and the A38G SNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…The levels of CC16 are lower in serum and nasal secretions of allergic children in comparison with healthy ones [14]. The concentrations of CC16 in nasal secretions of patients with seasonal allergic rhinitis are lower during the pollen season [11]. The results of one study concerning the role of CC16 in nasal inflammation in patients with PAR showed a positive correlation between the nasal fluid concentrations of CC16 and nasal production of nitric oxide (NO) [15].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The levels of CC16 are lower in serum and nasal secretions of allergic children in comparison with healthy ones [14]. The concentrations of CC16 in nasal secretions of patients with seasonal allergic rhinitis are lower during the pollen season [11]. The results of one study concerning the role of CC16 in nasal inflammation in patients with PAR showed a positive correlation between the nasal fluid concentrations of CC16 and nasal production of nitric oxide (NO) [15].…”
Section: Discussionmentioning
confidence: 95%
“…Previous investigations showed a suppressive effect of allergic inflammation on CC16 production [9,11,14]. The levels of CC16 are lower in serum and nasal secretions of allergic children in comparison with healthy ones [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the global proteome of these fluids are available, leading the path to their use for a biomarker discovery program. Genomic analyses can be carried out on the cells of nasal fluid or biopsy specimens (134)(135)(136).…”
Section: Proteomics and Genomicsmentioning
confidence: 99%